Triathlon Training Plan Preparation
As you know, your performance is improved through adaptation to progressively higher training stimulus. You can then work at a higher workload than that at which you previously fatigued. However, you will not adapt if you do not balance training stress and recovery, and your performance will suffer (Kuipers and Keizer 1988). People do not plan to fail, they simply fail to plan. Avoid this pitfall by establishing a smart training plan. Periodising Training The best way to combine the heavy periods of training with the periods of light training needed to allow adaptation and supercompensation is to periodise your training i.e.: cycle heavy, medium and light intensity work (Fry, Morton and Keast 1991). You could divide your training year into five patterns : base technique (BT) conditioning, endurance base (EB) conditioning , pre-season (PC), competition or peak transition (PT), and active rest (AR) cycles. These are discussed below. Different volumes and intensity of aerobic training, recovery training, sprint work, and threshold training should be emphasised in each cycle. I recommend doing mobility work all year round. It is important that you define your annual training periods, event, and training focus for each week and cycle according to your defined short and long-term goals. A systematic goal-setting process beginning with long-range goals that are divided into medium-range goals, which are again divided into more manageable short-range goals, is a smart starting point. Ensure that your training is patiently and purposely directed towards achieving your self-set goals. Never fall into the trap of trying to copy exactly what others do. It is better to train specifically based on your own ability.